Initiating Sunnah Ṡābitah And Sunnah Mutaghaiyyirāh as A Typology of The Prophet’s Sunnah in The Contemporary Era - Mohamad Nuryansah; Mokh Sya’roni; Eliza Agnesilviana (Millati: Journal of Islamic Studies and Humanities, 2023)
The position and function of the Prophet Muhammad (pbuh) in Islamic law is viewed differently among hadith scholars. The modern group of hadith experts see that there are two dimensions in the Prophet Muhammad (pbuh): the dimension as an apostle and the dimension as an ordinary human being. Meanwhile, the group of classical hadith experts believes that the Prophet Muhammad (pbuh) only has one dimension, namely, as an apostle. Classical hadith scholars argue that the Prophet Muhammad (pbuh) was a reflection of revelation, whether it was related to matters of sharia or related to humanity. The group of modern hadith experts made the concept of a prophet sunnah divided into sunnah tasri’iyyah and sunnah gairu tasyri’iyyah. Meanwhile, the group of classical hadith experts emphasizes that all of the Prophet’s sunnah are tasyri’iyah in nature. This paper aims to bridge the two groups of hadith experts by offering the terminology sunnah sābitah and sunnah mutaghaiyyirāh as an alternative typology of sunnah in the contemporary era. This paper is a descriptive-historical-reconstructive literature research using a history of ideas approach. The findings in this article are sunnah ṡābitah is a sunnah that must be implemented permanently regardless of time and place. In contrast, sunnah mutaghaiyyirāh is a sunnah of the Prophet whose implementation changes according to time and place. Sunnah ṡābitah is related to aqidah, worship, halal and haram, and general rules of muamalah. In addition to the four categories above, it is included in the sunnah mutaghaiyyirāh